Alleviating the adverse effects of salinity stress on Salicornia persica using sodium nitroprusside and potassium nitrate - Abbasali Moghaddam; Hamid Reza Larijani; Meysam Oveysi; Hamid Reza Tohidi Moghaddam; Mohammad Nasri (BMC Plant Biology, 2023)
Abstract Background Glasswort (Salicornia persica) is identified as a halophyte plant, which is one of the most tolerant plants to salt conditions. The seed oil of the plant contains about 33% oil. In the present study, the effects of sodium nitroprusside (SNP; 0, 0.1, 0.2, and 0.4 mM) and potassium nitrate (KNO3; 0, 0.5, and 1%) were evaluated on several characteristics of glasswort under salinity stress (0, 10, 20, and 40 dS/m). Results morphological features, phenological traits, and yield parameters such as plant height, number of days to flowering, seed oil, biological yield, and seed yield significantly decreased in response to severe salt stress. However, the plants needed an optimal salinity concentration (20 dS/m NaCl) to obtain high amounts of seed oil and seed yield. The results also showed that a high level of salinity (40 dS/m NaCl) caused a decrease in plant oil and yield. In addition, by increasing the exogenous application of SNP and KNO3, the seed oil and seed yield increased. Conclusions The application of SNP and KNO3 were effective in protecting S. persica plants from the deleterious effects of severe salt stress (40 dS/m NaCl), thereby restoring the activity of antioxidant enzymes, increasing the proline content, and maintaining cell membrane stability. It seems that both factors, i.e. SNP and KNO3, can be applied as mitigators of salt stress in plants.